Development and Performance Validation of a Prototype Digital pH and Temperature Meter for Consumer Applications - Ikhsan Siregar; Joiverdia Arifiyanto; Rulianda Purnomo Wibowo; Mahatir Muhammad (Postgraduate, University of Mataram, 2025)
This study aims to develop and evaluate an Arduino-based digital pH meter and thermometer prototype equipped with automatic temperature compensation (ATC) and a 3D-printed casing for practical household and micro-industrial applications. The device was tested on fifteen consumer products from four categories—food, beverages, hygiene, and cosmetics—at three temperature levels (30°C, 35°C, and 40°C). Measured parameters included pH, millivolt (mV) outputs, stabilization time, and reading stability. The results showed that pH values decreased with increasing temperature, consistent with H⁺ ion dissociation principles. For example, vinegar (pH 2.80–2.68) and soda (pH 3.45–3.36) showed the most significant decreases, while basic products such as detergent (pH 10.20–10.08) and liquid soap (pH 9.10–9.00) exhibited stable negative mV readings. The average stabilization time ranged from 6 to 12 seconds, with all samples showing stable readings (±0.01 pH variation). Calibration results indicated that three-point calibration (pH 4, 7, 10) produced the highest accuracy (±0.04 pH; R² = 0.993). The 3D-printed PLA casing provided durable protection, ergonomic handling, and fast reprintability. Overall, the prototype demonstrated reliable, accurate, and stable performance, proving that low-cost hardware and software integration can yield an efficient and accessible pH and temperature measuring tool.